Dioctadecyldimethylammonium:monoolein nanocarriers for efficient in vitro gene silencing - Oliveira, Ana Cristina Norberto Gonçalves (2014)
This study describes a novel liposomal formulation for siRNA delivery, based on the mixture of the neutral lipid monoolein (MO) and cationic lipids of the dioctadecyldimethylammonium (DODA) family. The cationic lipids dioctadecyldimethylammonium bromide (DODAB) and chloride (DODAC) were compared in order to identify which one will most efficiently induce gene silencing. MO has a fluidizing effect on DODAC and DODAB liposomes, although it was more homogeneously distributed in DODAC bilayers. All MO-based liposomal formulations were able to efficiently encapsulate siRNA. Stable lipoplexes of small size (100-160 nm) with a positive surface charge (>+45 mV) were formed. A more uniform MO incorporation in DODAC:MO may explain an increase of the fusogenic potential of these liposomes. The siRNA-lipoplexes were readily internalized by human nonsmall cell lung carcinoma (H1299) cells, in an energy dependent process. DODAB:MO nanocarriers showed a higher internalization efficiency in comparison to DODAC:MO lipoplexes, and were also more efficient in promoting gene silencing. MO had a similar gene silencing ability as the commonly used helper lipid 1,2-dioleyl-3-phosphatidylethanolamine (DOPE), but with much lower cytotoxicity. Taking in consideration all the results presented, DODAB:MO liposomes are the most promising tested formulation for systemic siRNA delivery.